Bridging the Gap: Financial Inclusion's Role in Environmental Sustainability in Pakistan - Muhammad Faheem; Asma Nousheen; Fatima Farooq; Muhammad Arshad Anwer (Journal of Accounting and Finance in Emerging Economies, 2023)
Purpose: The global impact of climate change on both human well-being and the environment has garnered widespread attention. Depending on the context, financial inclusion can either help people adapt to changing conditions or lessen the impact of those changes. The purpose of our research is to fill that study gap. While improved financial infrastructure is excellent for GDP, the only way to save the planet for both emerging and rich nations is through effective governance. This research looked at how different variables, such as financial inclusion (FINC), FDI, trade openness (TO), and economic growth (GDP), affects Pakistan's CO2 emissions and ecological footprint from 2004 to 2021.